Plan de negocios para la creación de una empresa productora y exportadora de una bebida energizante a base de Gingseng Inca y Pitahaya hacia Medellín, Colombia - Navas Zambrano, Alejandra Paola (2020)
The consumption of energy drinks have had a great impact on our society around the world, thanks to their miracle cures against fatigue and lack of rest, allowing a rapid response on vitality and energy to achieve regular activities. In a short amount of time this product has become one of the most popular and most sealed on the market. The problem begins when young and adult people start consuming this product on a daily basis, when this is one of the main reasons for heart diseases, causing major changes on the heart, brain and nervous system. Considering all this major affections on human beings the idea of elaborating a natural energy based on pitahaya and ging seng Inca was born. Giving the consumer a healthier alternative. This project will be placed in Quito, where all the producing cycle and fresco will be done and will be exported to Medellin, Colombia. This market was selected due to the constant change of a healthier version on the consumer favorite products. The research on the target market covers male and female consumers between the ages of 14 to 54 years old and middle, middle high and high socio economic stratum. Based on micro and meso analysis which was obtained about the status of the industry, main substitutes and competition. After that, based on a market investigation and a financial analysis which will achieve and deduct the viability of this business plan.